Beyond a~Shared History: A~Biosocial Perspective on Sociogenomics and Racism in Germany - Muna AnNisa Aikins; Yayouk Eva Willems; Deniz Fraemke; Laurel Raffington (KZfSS Kölner Zeitschrift für Soziologie und Sozialpsychologie, 2024)
Abstract Recent advances in sociogenomics offer new opportunities to integrate genetic and epigenetic measures into social science research on human lifespan development. Now, German social science cohorts have followed suit with this global trend. We anticipate that the integration of genetic measures into German social science cohorts is likely to be met with hesitation and dismay. Historically, racialized pseudo-science disguised as genetic research was used to justify the political exploitation, oppression, and genocide conducted by colonial and Nazi Germany regimes. In response, German institutions and social sciences actively avoided race-related research. However, avoiding the intersection of socially constructed race and genetics may stall the deconstruction of enduring racial discrimination and the identification of racialized social inequalities. Recent survey studies show that half of the German population still believe in the existence of biologically distinct human “races” and that racism is rampant. This article is aimed at providing a~biosocial perspective on sociogenomics and racism in Germany. First, we discuss the biologistic construction of race that became prevalent in colonial and Nazi Germany. We argue that racist legacies are sources of social inequality in contemporary German society. We further review recent human genomic science that clearly demonstrates that there is no biological basis to socially constructed race. Second, we propose a~biosocial perspective that integrates how genes “get out of the skin” and racism “gets under the skin”. Transactional genetic effects, which involve human behavior and interactions between people in society, are expected to depend on environmental inequalities tied to systemic racism. We summarize recent sociogenomics studies using polygenic indices and epigenetic profile scores showing that a)~genes contribute to complex human traits and b)~the expression of genetic variation is affected by socioeconomic and racialized inequality. Finally, we offer a~roadmap toward race-critical biosocial research that breaks with the historically informed avoidance of race to reconstruct race-critical concepts, datasets, and scientific systems. @Der Beitrag beleuchtet die jüngsten Fortschritte in der Soziogenomik und deren Potenzial, genetische und epigenetische Faktoren in die sozialwissenschaftliche Forschung zur menschlichen Entwicklung zu integrieren. Aus einer neuen biosozialen Perspektive auf Soziogenomik und Rassismus in Deutschland wird die Wechselwirkung zwischen Genen, menschlichem Verhalten, sozialen Interaktionen und Umweltfaktoren, insbesondere systemischem Rassismus, untersucht. Durch die Zusammenfassung aktueller soziogenomischer Studien wird verdeutlicht, dass Gene zu komplexen menschlichen Merkmalen beitragen und dass der Ausdruck genetischer Unterschiede von sozioökonomischen und rassifizierten Ungleichheiten beeinflusst wird. Im Beitrag wird außerdem die historisch vorherrschende biologistische Konstruktion von ,,Rasse“ im kolonialen und nationalsozialistischen Deutschland behandelt und aufgezeigt, wie dieses Erbe soziale Ungleichheit in der modernen deutschen Gesellschaft beeinflusst. Die aktuellsten Erkenntnisse der Humangenomik werden herangezogen, um eindeutig festzuhalten, dass es keine biologische Grundlage für das Konzept von ,,Rasse“ gibt. Abschließend bietet der Beitrag einen Ausblick auf rassismus-kritische biosoziale Forschung in Deutschland. Diese Forschung strebt an, Konzepte, Datensätze und wissenschaftliche Systeme rassismus-kritisch zu überprüfen und neu zu gestalten.
Keywords: 330; Genetics; Racism; Gene–environment interplay; Epigenetics; Germany; Social determinants of health; Genetik; Rassismus; Gen-Umwelt-Zusammenspiel; Epigenetik; Deutschland; Soziale Determinanten der Gesundheit